Corynebacterium urealyticum Urinary Tract Infections in Pediatric Renal Transplant Recipients: Clinical Spectrum and Management Strategies - Guyu Li; Alicia Morales; Elizabeth Ristagno; Anna Huppler; Nipunie Rajapakse (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Pediatric renal transplant recipients are at increased risk for Corynebacterium urealyticum urinary tract infections (UTIs), which can range from simple nephritis to encrusted pyelitis and infected nephrolithiasis. Limited data exist regarding clinical spectrum and standardized management strategies, contributing to variability in treatment and prognosis. We describe two pediatric renal transplant recipients with C. urealyticum-associated encrusted pyelitis and infected nephrolithiasis and outline their clinical management and outcomes. Methods A retrospective review was conducted at Mayo Clinic, Rochester, identifying pediatric patients (aged 0-18 years) who underwent renal transplantation between January 1, 2012, and January 1, 2025, and subsequently developed C. urealyticum UTI. Demographic characteristics, microbiologic findings, and clinical courses were summarized (Table). Results Case 1 A 14-year-old female with stage 5 chronic kidney disease secondary to complex congenital urologic anomalies developed multiple renal calculi in the right transplant allograft pelvis and proximal ureter four years after transplantation (Figure). Despite repeatedly negative urine cultures, C. urealyticum was isolated from the stone culture after 72 hours of incubation. The patient underwent stone removal, completed a 2-week course of oral linezolid, and was transitioned to oral doxycycline for 6 months as chronic suppressive therapy due to better tolerability. At one-year follow-up, there was no recurrence of renal stones or UTI. Case 2 A 4-year-old male with Prune-Belly syndrome and chronic kidney disease developed gross hematuria and passed small stones six weeks after renal transplantation. Although initial urine cultures were not tested for C. urealyticum, cultures obtained eight months later grew C. urealyticum. He was found to have encrusted pyelitis and renal stones involving the calyces and transplant ureter, requiring stenting, multiple debulking procedures, and nephrolithotomy. He received eight weeks of sequential antibiotic therapy with linezolid, azithromycin, and doxycycline, along with Renacidin for urine acidification and vancomycin flushes through the nephrostomy tube. Despite these interventions, intractable encrusted pyelitis led to transplant nephrectomy. After a second renal transplant, he received perioperative linezolid for 10 days, with no recurrence at one-year follow-up. Conclusion These cases underscore the importance of recognizing C. urealyticum as a potential pathogen in pediatric renal transplant recipients presenting with nephrolithiasis or encrusted pyelitis. Because of its slow growth, prolonged incubation of urine or stone cultures is recommended to facilitate detection. Empiric therapy with linezolid or vancomycin may be appropriate while awaiting susceptibility results. Timely stone removal and chronic suppressive therapy may be utilized to prevent recurrence and preserve allograft function.